Starch-based hard carbon material, preparation thereof and application of starch-based hard carbon material in sodium-ion battery
Through the combined pretreatment and carbonization of starch raw materials and halogen elements in an oxygen-containing atmosphere, the problem of starch-based hard carbon materials easily expanding and powdering during the preparation process is solved, and high-efficiency and low-energy-consumption type-retaining carbonization is achieved, which improves the high temperature and high rate performance of the material, and is suitable for the negative electrode material of sodium ion batteries.
Patent Information
- Application Number
- CN202411985607.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Starch-based hard char material is prone to expanding and powdering during the preparation process, making it difficult to maintain the shape, and its preparation efficiency and high temperature and high rate performance of the material are not ideal.
The combined pretreatment of starch raw materials and halogen elements (such as iodine) in an oxygen-containing atmosphere is adopted, and then carbonization is carried out to inhibit the foaming and powderization of the starch and improve the physical and chemical structure, and improve the carbon yield and electrochemical properties.
It realizes high efficiency, low energy consumption and type-resisting carbonization of starch-based hard carbon materials, and has excellent high temperature and high rate performance, and is suitable for the negative electrode materials of sodium ion batteries.
Smart Images

Figure CN119750545A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and specifically to the field of hard carbon materials for sodium ion batteries. Background Art
[0002] Lithium-ion batteries are one of the fastest-growing and most commercially promising electrochemical energy storage systems. Over the past few years, lithium-ion batteries have been widely used in portable electronics, driving the development of next-generation electric vehicles due to their high energy density and long cycle life. Although there may not be a lithium shortage in the short term, the increasingly depleted resources will pose a challenge to the long-term large-scale industrial development of lithium batteries. Unlike lithium, sodium is abundant, low-cost, and globally available, and can be obtained from minerals and brine. Therefore, sodium-ion batteries are considered to be the most promising candidate to replace lithium-ion batteries for large-scale energy storage applications, which is a key step in the development of sustainable renewable energy systems. However, the radius of sodium ions is larger than that of lithium ions, and the graphite anode widely used in lithium-ion batteries is not suitable for the insertion and extraction of sodium ions due to the small interlayer spacing. In contrast, hard carbon with high disorder and large interlayer spacing has a high sodium storage capacity as the anode of sodium-ion batteries as well as good cycle stability.
[0003] Hard carbon precursors mainly come from biomass and polymers. Among them, biomass-derived carbon has become the material technology system for the industrialization of hard carbon. However, due to the activation of impurities during pyrolysis, biomass-derived carbon has a large specific surface area, resulting in a lower first coulombic efficiency. Therefore, biomass-derived carbon needs to undergo acid treatment or other surface treatments to improve the material microstructure and reduce the specific surface area. In contrast, polymer precursors with low impurity content are easy to achieve fine microstructure control to obtain better electrochemical performance. Among them, starch can be produced from various high-yield food crops such as corn, potatoes, rice, etc., and has a wide source and a stable supply system.
[0004] For example, a Chinese patent document with publication number CN118439586A discloses a method for preparing a starch-based hard carbon negative electrode material, in which starch and tannic acid are dissolved in a sulfuric acid solution of a certain concentration, heated and stirred for a certain period of time, the resulting product is filtered several times to remove residual sulfuric acid, and the treated material is carbonized at high temperature in a nitrogen atmosphere to obtain a starch-based hard carbon negative electrode material. For another example, a Chinese patent document with publication number CN118439588A discloses a starch-based hard carbon negative electrode material and a preparation method thereof, comprising the following steps: S1. Heating the starch to a first temperature of 200-250°C at a first heating rate, and maintaining the first holding time for 8-30 hours to obtain a starch-based hard carbon precursor; S2. Heating the starch-based hard carbon precursor obtained in step S1 to a second temperature of 550-650°C at a second heating rate under an inert atmosphere, and maintaining the second holding time for 1-4 hours to obtain a starch-based hard carbon intermediate; S3. The starch-based hard carbon intermediate obtained in step S2 is further heated to a third temperature of 1400-1600°C at a third heating rate, and maintained for a third holding time of 1-4 hours to obtain a starch-based hard carbon negative electrode material.
[0005] Although starch has many advantages in preparing hard carbon, starch will produce cross-linking and foaming during heat treatment, and its volume will expand several times. In this process, the carbon-oxygen ring of starch will be dehydrated to produce L-glucose, which will eventually be converted into tar and oxygen-containing compounds, reducing production efficiency and losing its original nearly spherical morphology. In order to inhibit starch cross-linking and foaming, it usually takes more than 20 hours of pretreatment, which increases the energy consumption of actual production and reduces production efficiency. Summary of the invention
[0006] In view of the problems that existing starch-based hard carbon materials are easy to expand and powderize, difficult to prepare with shape retention, and the preparation efficiency as well as the fast charging and high-temperature performance of the prepared materials are not ideal, the present invention provides a method for preparing starch-based hard carbon materials, aiming to provide a method with high efficiency, low energy consumption, shape retention carbonization and the ability to produce starch-based hard carbon materials with excellent high-temperature and high-rate performance.
[0007] The second purpose of the present invention is to provide a starch-based hard carbon material obtained by the preparation method and its application in sodium ion batteries.
[0008] The third object of the present invention is to provide a sodium ion battery comprising the starch-based hard carbon material and its negative electrode and negative electrode material.
[0009] When starch is used to prepare hard carbon, there is an obvious problem of foaming and powdering. To address this problem, the main idea in the industry is to add other auxiliary carbon sources or extend the low-temperature treatment time. This solution will affect the preparation efficiency. In addition, it is easy to cause the original morphology to become powdery and deteriorate, affecting the electrochemical performance of the material at high rates and high temperatures. To address this problem, the present invention has conducted in-depth research and provided the following improvement scheme:
[0010] A method for preparing a starch-based hard carbon material, comprising pretreating a starch raw material and X2 in an oxygen-containing atmosphere at a temperature of 100 to 400° C., and then carbonizing the starch raw material to obtain the hard carbon material;
[0011] In the X2, X is a halogen element.
[0012] In order to solve the problems faced by starch raw materials in the process of preparing hard carbon, such as easy foaming and powdering, low preparation efficiency, difficulty in maintaining shape during carbonization, and low carbon yield and high-temperature and high-rate performance of the material, the present invention innovatively pretreats the starch raw materials and X2 in an oxygen-containing atmosphere, and then performs a carbonization treatment. This can solve the above-mentioned problems faced by starch in the process of preparing hard carbon, and can produce hard carbon materials with excellent performance, especially high capacity, high rate and high-temperature stability, with high efficiency, high shape retention and high carbon yield without the assistance of other carbon sources.
[0013] In the present invention, the starch raw material may include, for example, one or more of corn starch, tapioca starch, potato starch, rice starch, wheat starch, and potato starch.
[0014] Preferably, the starch raw material has a spherical or spherical-like morphology.
[0015] In the present invention, starch is treated jointly with X2 and an oxygen-containing atmosphere. Based on the physicochemical characteristics of X2 and the oxygen-containing atmosphere, the starch structure can be stabilized and the risk of foaming and powdering can be reduced. In addition, its physicochemical structure can be optimized, which is beneficial to the subsequent carbonization to construct the physicochemical structure characteristics of sodium-electricity adaptation, thereby improving the sodium-electricity performance of the prepared material.
[0016] In the present invention, X is Cl, Br or I.
[0017] Preferably, X is I, and the starch raw material and X2 are premixed and then pretreated. The present invention shows that when X is I, the thermal gasification of I2 and the synchronous combination of gasified I2 and oxygen-containing atmosphere can further optimize the physicochemical structure of starch, and the starch hard carbon can be further prepared with shape retention, high efficiency and high carbon yield. Not only that, it is also conducive to the preparation of materials that are more suitable for sodium battery application requirements and can exhibit better capacity, high rate and high temperature performance.
[0018] In the present invention, when the initial state of X2 is gaseous, its volume proportion in the pretreatment atmosphere can be 1-70v%, preferably 5-30v%. When the initial state of X2 is liquid or solid, the weight ratio of the starch raw material and X2 can be controlled to be 0.1-10:1, preferably 1-5:1, and more preferably 1-2:1. The present invention also shows that controlling the ratio can further enhance the synergy of the process, and can further improve the preparation effect and the performance of the prepared material at high rate and high temperature.
[0019] In the present invention, the oxygen-containing atmosphere is an atmosphere containing at least one functional gas of oxygen and ozone. The content of the functional gas in the oxygen-containing atmosphere may be 10-30v%; in consideration of cost, it may further be air.
[0020] Preferably, the pretreatment temperature is 200-280°C.
[0021] Preferably, the holding time at the pretreatment temperature is 1 to 24 hours, preferably 2 to 12 hours, and further can be 4 to 6 hours.
[0022] In the present invention, the carbonization temperature is 1000-2800° C., preferably 1100-1400° C. Studies have shown that at the preferred temperature, it can be combined with other processes to further solve the problems existing in the preparation of hard carbon from starch, and better performance can be obtained.
[0023] Preferably, the holding time at the carbonization temperature is 0.5 to 10 hours, and further can be 1 to 3 hours.
[0024] Preferably, before the carbonization treatment, a pre-carbonization process is also included at a temperature of 300-950°C; preferably 350-650°C; more preferably 400-500°C. Studies have shown that under the preferred pre-carbonization, the pre-carbonization temperature can be combined with other processes to further solve the problems existing in the preparation of hard carbon from starch, and better performance can be obtained.
[0025] Preferably, the holding time at the pre-carbonization temperature is 0.5 to 10 hours, and further can be 1 to 3 hours.
[0026] The atmosphere during the carbonization and pre-carbonization process is a protective atmosphere, such as at least one of nitrogen and an inert gas.
[0027] The present invention also includes a starch-based hard carbon material prepared by the preparation method.
[0028] The preparation method described in the present invention can give the material physicochemical characteristics that are compatible with sodium batteries, and the material prepared by the preparation method can exhibit excellent capacity, high rate and high temperature performance in sodium battery applications.
[0029] The present invention also provides a negative electrode material for a sodium ion battery, comprising a negative electrode active material, wherein the active material comprises a starch-based hard carbon material obtained by the preparation method;
[0030] In the present invention, in the negative electrode active material, the content of the starch-based hard carbon material is above 50wt.%;
[0031] In the negative electrode material, the content of the negative electrode active material is above 60wt.%, and further 70-95wt.%;
[0032] In the present invention, the negative electrode material further comprises a conductive agent and a binder which are allowed to be added in the field of sodium ion batteries;
[0033] In the present invention, the content of the conductive agent and the binder can be adjusted as needed, for example, it can be below 15 wt.%.
[0034] The present invention also provides a negative electrode of a sodium ion battery, comprising a current collector and a negative electrode material composited on the current collector, wherein the negative electrode material comprises the starch-based hard carbon material obtained by the preparation method.
[0035] The present invention also provides a sodium ion battery, which comprises the negative electrode containing the starch-based hard carbon material described in the present invention.
[0036] The sodium ion battery and its negative electrode and negative electrode material described in the present invention, in addition to comprising the starch-based hard carbon material prepared by the preparation method described in the present invention, other components, parts and structures can be known in the field of sodium ion batteries.
[0037] Beneficial Effects
[0038] The present invention innovatively adopts X2 and oxygen-containing atmosphere to pre-treat and modify starch, which can inhibit the dehydration reaction of C6 hydroxyl and C1 hydroxyl in the carbon-oxygen ring of starch molecules to convert into harmful levorotatory glucose, promote the dehydration between starch molecular chains, improve production efficiency, reduce energy consumption, and further improve the carbon yield, achieve shape-preserving preparation, and prepare sodium-based materials with excellent rate and high-temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the SEM image of the starch pretreated in step 2 of Example 1;
[0040] Figure 2 This is a SEM image of the hard carbon negative electrode material finally obtained in step 3 of Example 1;
[0041] Figure 3 It is a comparison diagram of room temperature charge and discharge curves of the hard carbon negative electrode materials in Example 1, Example 2, and Comparative Example 2;
[0042] Figure 4 It is a comparison diagram of the rate charging curves of the hard carbon negative electrode materials in Example 1, Example 2, and Comparative Example 2;
[0043] Figure 5 This is the 40°C high temperature charge and discharge curve of the hard carbon negative electrode material in Example 1;
[0044] Figure 6 Foaming diagram of the pre-carbonized material in Comparative Example 1;
[0045] Figure 7 SEM image of the carbonized hard carbon negative electrode material in Comparative Example 1;
[0046] Figure 8 SEM image of the hard carbon negative electrode material in Comparative Example 5. DETAILED DESCRIPTION
[0047] The present invention will be further described in detail below in conjunction with specific examples. The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the scope of protection of the invention.
[0048] Example 1
[0049] The present invention provides a technical solution as follows: a method for preparing a hard carbon negative electrode material, comprising the following steps:
[0050] (1) Raw material preparation: Weigh a certain amount of corn starch raw material and mix it evenly with iodine, with the mass ratio of corn starch to iodine being 1:1;
[0051] (2) The mixture in step (1) was placed in a tube furnace, air atmosphere was introduced, and the temperature was raised to 220°C (marked as T1) at a rate of 1°C / min, and the insulation time was 6 hours. After the insulation was completed, the pretreated material was obtained. SEM Figure 1 .
[0052] (3) The material pretreated in step (2) was placed in a tube furnace, heated to 400°C (marked as T2) at a rate of 5°C / min in an argon atmosphere, and pre-carbonized for 2 hours. Then, the temperature was raised to 1200°C (marked as T3) at a rate of 5°C / min, and carbonized for 2 hours. After cooling, a hard carbon spherical negative electrode material was obtained. The carbon yield was 26.8%, and SEM showed that Figure 2 .
[0053] The specific surface area of the hard carbon microspheres obtained in this example is 1.5 m 2 / g, and the carbon layer spacing is 0.42nm.
[0054] test
[0055] The hard carbon spherical negative electrode active material obtained in step 3, conductive carbon (conductive carbon black), styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a mass ratio of 9:2:1.8:1.2 to prepare a uniform slurry, and the slurry was evenly coated on the aluminum foil current collector and then placed in a drying oven at 100°C for 12 hours. The hard carbon electrode obtained in this embodiment was punched into a small disc with a diameter of 10 mm, and the density of the active material loaded was about 2 mg cm -2 , as the working electrode. Glass fiber (Whatman, f-type) was used as a separator, metallic sodium was used as a counter electrode, the electrolyte was a sodium hexafluorophosphate solution (the concentration of sodium hexafluorophosphate was 1 M, and the solvent was a mixed solution of ethyl carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1), and a CR2032 button cell was assembled.
[0056] The battery undergoes electrochemical performance testing:
[0057] (1) The electrochemical performance test was carried out at room temperature with a current density of 30 mA / g and a voltage range of 0-2 V. The first cycle charge capacity at room temperature was 335.82 mAh / g, the first cycle coulombic efficiency was 88.63%, and the charge and discharge curves were shown in Figure 3 .
[0058] (2) At room temperature, the charge rate test was performed at 0.1C, 0.3C, 0.5C, 1C, 1.5C, 2C, 3C, and 5C. Each current cycle was 5 cycles, and then returned to 0.1C for 10 cycles. The discharge current was fixed at 0.1C and the voltage range was 0-2V. The specific capacity of the 5C charge rate at room temperature was 276.3mAh / g. Figure 4 .
[0059] (3) Electrochemical performance test was carried out at 40°C, current density 30mA / g, voltage range 0-2V. The first cycle charge capacity at 40°C was 434.3mAh / g, the first cycle coulombic efficiency was 87.46%, and the charge and discharge curves were shown in Figure 5 .
[0060] Example 2
[0061] Compared with Example 1, the only difference is that in step 1, the corn starch raw material and iodine are uniformly mixed in a mass ratio of 4:1; in step 2, the temperature T1 is 250° C. and the insulation time is 4 h; other operations and parameters are the same as in Example 1, and the test is carried out according to the method of Example 1, and the results are:
[0062] The carbon yield is 23.8%; the first cycle charge capacity at room temperature and 30 mA / g is 316.4 mAh / g, the first cycle coulomb efficiency is 90.56%, and the charge and discharge curves are shown in Figure 3 The room temperature 5C rate charge capacity is 244.4mAh / g, see Figure 4The first cycle charge capacity at 40°C is 388.7 mAh / g, and the first cycle coulombic efficiency is 88.8%.
[0063] Example 3
[0064] Compared with Example 1, the only difference is that the X element composition is changed. The experimental groups are:
[0065] Group A: A certain amount of corn starch was placed in a quartz tube and chlorine vapor was introduced, with the volume ratio of chlorine vapor to air atmosphere being 2:8;
[0066] Group B: A certain amount of corn starch raw material was uniformly mixed with bromine solution, and the mass ratio of corn starch to bromine was 1:1. Other operations and parameters were the same as those in Example 1, and the electrochemical performance test (1) was carried out according to the method of Example 1. The results were:
[0067] Group A: The carbon yield was 23.5%; the first cycle charge capacity at room temperature and 30 mA / g was 306.2 mAh / g, and the first cycle coulombic efficiency was 86.5%;
[0068] Group B: The carbon yield was 22.2%; the first cycle charge capacity at room temperature and 30 mA / g was 303.4 mAh / g, and the first cycle coulombic efficiency was 87.8%.
[0069] Example 4
[0070] Compared with Example 1, the only difference is that the conditions of step 2 are changed, and the experimental groups are: the oxygen-containing atmosphere is 30v% oxygen-argon atmosphere, T1=260°C, the heating rate is 2°C / min, and the holding time is 6h;
[0071] Other operations and parameters were the same as those in Example 1, and the electrochemical performance test (1) was carried out according to the method in Example 1. The results were as follows: the carbon yield was 21.7%; the first-cycle discharge capacity at room temperature and 30 mA / g was 310.1 mAh / g, and the first-cycle coulomb efficiency was 88.2%.
[0072] Example 5
[0073] Compared with Example 1, the only difference is that the conditions of step 3 are changed, and the experimental groups are:
[0074] Group A: no T2 insulation process;
[0075] Group B: T2 = 600°C, heating 5°C / min, holding time 1h; T3 = 1000°C, heating 10°C / min, holding time 1h;
[0076] Other operations and parameters were the same as those in Example 1, and the electrochemical performance test (1) was carried out according to the method in Example 1. The results were:
[0077] Group A: The carbon yield was 25.5%; the first cycle charge capacity at room temperature and 30 mA / g was 295.5 mAh / g, and the first cycle coulombic efficiency was 83.3%;
[0078] Group B: The carbon yield was 24.1%; the first cycle charge capacity at room temperature and 30 mA / g was 285.7 mAh / g, and the first cycle coulombic efficiency was 86.6%.
[0079] Comparative Example 1
[0080] Compared with Example 1, the only difference is that in step 1, iodine is missing. The other operations and parameters are the same as those in Example 1. The electrochemical performance test (1) is carried out according to the method of Example 1. The results are as follows: foaming and expansion after pre-carbonization (T2 temperature) (see Figure 6 ), SEM after carbonization Figure 7 , the carbon yield is 19.3%; the first cycle discharge capacity at room temperature and 30mA / g is 255.3mAh / g, and the first cycle coulombic efficiency is 78.6%;
[0081] Comparative Example 2
[0082] Compared with Example 1, the only difference is that in step 1, iodine is lacking, and the holding time in step 2 is extended to 72h. The other operations and parameters are the same as those in Example 1. The test is carried out according to the method of Example 1. The results are: the carbon yield is 20.3%; the first cycle discharge specific capacity at room temperature is 300.7mAh / g, the first cycle coulomb efficiency is 85.43%, and the charge and discharge curves are shown in FIG. Figure 3 The room temperature 5C rate charge capacity is 240.5mAh / g, see Figure 4 The first cycle charge capacity at 40°C and 30 mA / g is 365.6 mAh / g, and the first cycle coulombic efficiency is 83.8%.
[0083] It can be seen from Example 1, Example 2, Comparative Example 1 and Comparative Example 2 that the addition of iodine and the control of the mass ratio of starch to iodine significantly improve the starch processing efficiency, and ultimately significantly improve the first efficiency, first cycle capacity, high rate performance and high temperature performance of the hard carbon negative electrode sodium ion battery.
[0084] Comparative Example 3
[0085] Compared with Example 1, the only difference is that in step 2, nitrogen is used to replace the air. The other operations and parameters are the same as those in Example 1, and the electrochemical performance test (1) is carried out according to the method of Example 1. The results are as follows: the starch foams and expands after carbonization, and the carbon yield is 20.5%; the first cycle discharge specific capacity at room temperature and 30 mA / g is 264.3 mAh / g, and the first cycle coulomb efficiency is 77.5%;
[0086] Comparative Example 4
[0087] Compared with Example 1, the only difference is that the treatment of step 2 is not carried out, and the mixture is directly subjected to the operation of step 3. The other operations and parameters are the same as those of Example 1. The electrochemical performance test (1) is carried out according to the method of Example 1. The results are: the starch foams and expands after carbonization, and the carbon yield is 18.5%; the first-cycle discharge specific capacity at room temperature and 30mA / g is 234.7mAh / g, and the first-cycle coulomb efficiency is 64.4%.
[0088] Comparative Example 5
[0089] Compared with Example 1, the only difference is that in step 1, ammonium iodide is used instead of iodine (the amount of iodine element is the same as in Example 1), and the other operations and parameters are the same as in Example 1. The electrochemical performance test (1) is carried out according to the method of Example 1. The results are: the carbon yield is 23.3%; the first-cycle discharge capacity at room temperature and 30 mA / g is 285.6 mAh / g, the first-cycle coulomb efficiency is 83.6%, and the spherical morphology of the starch is corroded, as shown in SEM. Figure 8 .
[0090] Comparative Example 6
[0091] Compared with Example 1, the only difference is that step 3 is omitted, and the other operations and parameters are the same as those of Example 1. The electrochemical performance test (1) is carried out according to the method of Example 1. The results are: the carbon yield is 19.4%; the first cycle discharge specific capacity at room temperature and 30 mA / g is 257.3 mAh / g, and the first cycle coulomb efficiency is 79.8%;
[0092] To sum up, the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Various modifications, variations and improvements made to the technical solution of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a starch-based hard carbon material, characterized in that: The starch raw material and X2 are pretreated in an oxygen-containing atmosphere at a temperature of 100 to 400° C., and then carbonized to obtain; In the X2, X is a halogen element.
2. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: The starch raw material may include, for example, one or more of corn starch, tapioca starch, potato starch, rice starch, wheat starch, and potato starch; Preferably, the starch raw material has a spherical or spherical-like morphology.
3. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: The X is Cl, Br or I.
4. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: The X is I, the starch raw material and X2 are pre-mixed and then pre-treated; Preferably, the weight ratio of the starch raw material to X2 is 0.1 to 10:1, preferably 1 to 5:1, and more preferably 1 to 2:
1.
5. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: The oxygen-containing atmosphere is an atmosphere containing at least one functional gas of oxygen and ozone; Preferably, the pretreatment temperature is 200-280°C; Preferably, the holding time at the pretreatment temperature is 1 to 24 hours, preferably 2 to 12 hours.
6. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: The carbonization temperature is 1000~2800℃; Preferably, the holding time at the carbonization temperature is 0.5 to 10 hours; Preferably, before the carbonization treatment, a pre-carbonization process is further included at a temperature of 300 to 950°C; preferably 350 to 650°C; more preferably 400 to 500°C; Preferably, the holding time at the pre-carbonization temperature is 0.5 to 10 hours; The atmosphere of the carbonization process is a protective atmosphere, for example, at least one of nitrogen and an inert gas.
7. A starch-based hard carbon material obtained by the preparation method according to any one of claims 1 to 6.
8. A negative electrode material for a sodium ion battery, characterized in that: It comprises a negative electrode active material, wherein the active material comprises a starch-based hard carbon material obtained by the preparation method.
9. A negative electrode of a sodium ion battery, characterized in that: It comprises a current collector and a negative electrode material composited on the current collector, wherein the negative electrode material is the negative electrode material according to claim 8.
10. A sodium ion battery, characterized in that: The negative electrode according to claim 9 is included.
Citation Information
Patent Citations
Sodium metaaluminate-coated core-shell type hard carbon composite material as well as preparation method and application thereof
CN116864655A
High-rate coal-based hard carbon composite negative electrode material, preparation method thereof and sodium ion battery
CN117133900A
Starch-based hard carbon material as well as preparation method and application thereof
CN118306977A
Starch-based hard carbon negative electrode active material, preparation thereof and application of starch-based hard carbon negative electrode active material in sodium-ion battery
CN118458748A
Modified porous amorphous carbon negative electrode material as well as preparation method and application thereof
CN118841546A